Hubungan Pola Asuh Orang Tua dengan Motivasi Belajar Siswa Kelas 4 SD Negeri 064027 Medan Polonia - Anis Fitria Harahap (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to find a significant relationship between parental care in class IV of SD Negeri 064072 Medan Polonia and their motivation to study with the research title